Hamnet : [book club bag] a novel of the plague - O'Farrell, Maggie, 1972- (Alfred A. Knopf, 2020)
"A thrilling departure: a short, piercing, deeply moving novel about the death of Shakespeare's 11 year old son Hamnet--a name interchangeable with Hamlet in 15th century Britain--and the years leading up to the production of his great play. England, 1580. A young Latin tutor--penniless, bullied by a violent father--falls in love with an extraordinary, eccentric young woman--a wild creature who walks her family's estate with a falcon on her shoulder and is known throughout the countryside for her unusual gifts as a healer. Agnes understands plants and potions better than she does people, but once she settles with her husband on Henley Street in Stratford she becomes a fiercely protective mother and a steadfast, centrifugal force in the life of her young husband, whose gifts as a writer are just beginning to awaken when his beloved young son succumbs to bubonic plague. A luminous portrait of a marriage, a shattering evocation of a family ravaged by grief and loss, and a hypnotic recreation of the story that inspired one of the greatest masterpieces of all time, Hamnet is mesmerizing, seductive, impossible to put down--a magnificent departure from one of our most gifted novelists"--